Fistula Prevention Awareness - Siddiqui, Sajjad Ahmed (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: Genital tract fistula is a known tragedy in Pakistan. We know the causes of this tragedy and we also know the methods to eradicate this curse from the community. Despite the initiative from UNFPA, Islamic Development Bank and other concerned stake holders the government of Pakistan has failed to address the issue and an organized system is not developed to reduced maternal death rate and maternal morbidity in Pakistan. It’s a common practice to exploit the sad situation of victims of fistula and run ghost campaigns to eradicate genital tract fistula from the community. Methods:In depth analysis on intersections of social inequities in health, polices in Pakistan. The review carried out on the available literature / reports around the theme of women health & rights responsiveness in health systems. This analysis also includes the role and support of the donor agencies working on maternal health in Pakistan. Results: An overall unfairness prevailing in the healthcare system which is affecting women health resulting a very high maternal mortality ratio (MMR) maternal morbidity like fistula. The health policy is a highly complex phenomenon needs a multi-disciplinary approach to develop public policy that aims to explain the interaction between institutions, interests and ideas in the policy process. Health policies must reflect the specific steps to address the issue of gender based discrimination. Conclusion: The politics of fistula is serving people to become rich in vested interest group, its providing platform to governments to make their image in front of donor countries. It’s also providing opportunity to people working in donor agencies to get involve in corruption at the cost of poor patients of fistula. Prevention of fistula is ultimate goal to get rid of this morbidity need department of health for provision of basic health facilities specially availability of SBA BUT there is no such policy intervention to produce competent midwives local community level. The existing fistula cases are not treated at district level due to lack of skill of local gynecologists to repair the fistula at district level.